Dystocia due to Schistosomus reflexus in a Jersey Crossbred Cow - Kumar, Pravesh; Sharma, Amit; Singh, Madhumeet; Bhardwaj, Neelam (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Congenital anomalies, and less frequently multiple congenital anomalies, are encountered in domestic animals, which in turn may cause obstetrical problems (Noakes et al., 2002). Schistosomus reflexus is characterized by anomaly of the trunk with actual angulation of vertebral column, herniation of abdominal organs and skeleton defects leading to dystocia. Only cases that display both visceral exposure and spinal inversion are considered as true Schistosomus reflexus (Laughton et al., 2005). The condition is a type of monstrosity reported most commonly in cattle (Knight, 1996; Kalirajan and Rani, 2016; Prabaharan et al., 2016), buffalo (Kumar et al., 2012), sheep (Mukasa Mugerwa and Bekele, 1989) and goats (Barman et al., 2010). The prevalence of Schistosomus reflexus is believed to occur in cattle from as low as 0.01% (Sloss and Johnston, 1967) to 1.3% (Knight, 1996).